Deoxypyridinoline and mineral levels in gingival crevicular fluid as disorder indicators of menopausal women with periodontal disease - Agustin Wulan Suci Dharmayanti; Banun Kusumawardani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Menopause is a phase of a woman’s life marked by menstruation cycle cessation and an increased risk of periodontal disease. It can be caused by estrogen deficiency which alters the microenvironment in the sulcular gingival area and influences the composition and flow of gingival crevicular fluid (GCF). GCF has been widely studied as a non-invasive diagnostic and predictive tool for periodontal diseases. However, insufficient reports exist that explore its role as a predictive or diagnostic tool for bone loss detection in menopausal women. Purpose: This study aimed was to investigate deoxypyridinoline (DPD) and mineral levels that could be utilized as disorder indicators in menopausal women with periodontal disease. Methods: This study represents a form of analytical observation. Eighty-four patients of the Dental Hospital, University of Jember who fulfilled certain criteria were recruited. The subjects were divided into two main groups based on the presence of periodontal disease, (gingivitis=26; periodontitis=58) which were subsequently divided into three sub-groups based on their menopausal phase (pre-menopausal=26; perimenopausal=40; post-menopausal=18). GCF was collected using paper points from the buccal site of a posterior maxillary tooth with each subject having their GCF taken on only one occasion. DPD analysis was conducted by means of an ELISA test. The analysis of calcium, magnesium and sodium incorporated the use of an Atomic Absorption Spectroscope (AAS), while that of phosphor was by means of a spectrophotometer. Statistical analyses were performed using a comparison and correlation test (p<0.05). Results: There were significant differences in DPD and the mineral level of GCF in menopausal women with periodontal diseases (p<0.05). DPD and mineral levels showed significant correlation to those of menopausal women with periodontal diseases and a pH of GCF. Conclusion: DPD and mineral level in GCF could be used as disorder indicators in menopausal women with periodontal diseases.